Adat Pengantin Nusantara Melayu Riau Dalam Pengembangan ‎Budaya - Farhan Aditya; Ismail Pane (Indra institute Research & Publication, 2023)
The goal of this research is to evaluate how the description of the bride Malay Ujungbatu Riau's indigenous culture affecting the progress of civic culture. The indigenous culture of the bride, the Malay Ujungbatu, is looked into and studied in the development of civic culture. The findings of this study demonstrate that a) the Malay Ujung Batu bride custom culture test setup from menjalang mamak, kampung suku, kampung penghulu, and menjalang mintuo. As discussing civic culture, it is important to remember that: a) the Malay Ujung Batu procession of the bride will include: antar tanda, khatam Al-Qur'an, tepung tawar, berinai, ber-arak, or ber-dikie. The importance of belief, attitude, ability to cooperate, solidarity, unity, responsibility, and reciprocal collaboration is seen in the context of civic culture. because civic education (PKn) is a natural element of family and societal life. The research focuses on indigenous people, young people, and society. Both the indigenous figure and the parents in a family atmosphere are simultaneously encouraging the preservation efforts. It can be said that the indigenous Ujungbatu Riau Malay people possess civic cultural values as a result of the development of civic culture..